Pentingnya Peranan Roh Kudus Terhadap Pendirian Jemaat - Grace Na Anantha Lumban Tobing; Rike Yohana Simatupang; Rame Syahputri Br.Regar; Kasih Natalouis Simamora; Nata Nael Pasaribu; Rizky Januaris Pardede; Megawati Manullang (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Congregational establishment is a process in which a group of people decide to form an ecclesiastical community. The Holy Spirit played a very important role in the founding of the Christian community. In the early church founded by the apostles the role of the Holy Spirit was very important. The Holy Spirit who indwells everyone who has believed in Christ makes their lives change drastically. By using qualitative research methods by collecting several sources and books. With the aim of knowing the importance of the role of the holy spirit itself in the establishment of the church.